Hubungan Antara Perhatian Orang Tua Dengan Hasil Belajar Siswa kelas III SDN Gugus 14 Kota Bengkulu - Aranita, Septi; Anggraini, Dwi (Universitas Bengkulu, 2024)
The success of students' learning outcomes depends on various factors, and parental attention is one of the crucial elements among them.This study aims to determine the relationship between parental attention and the learning outcomes of class III students at SDN Gugus 14 Bengkulu City. The population of this research comprises 310 class III students, with a sample size of 47 students from SDN Gugus 14 Bengkulu City. It is a quantitative research using the correlation method. The research instruments consist of questionnaires to assess parental attention and documentation of learning outcomes in the mid-even semester assessment for the 2022/2023 Academic Year. Data analysis is performed using the